Uso de plantas medicinales como alternativa de tratamiento en infecciones urinarias: revisión bibliográfica - Chimbo Pacheco, Marilu Alexandra (2025)
The use of medicinal plants as an alternative treatment for urinary tract infections has gained increasing attention in the scientific field, especially in an era where antibiotic resistance is a significant global health challenge. Objective: To analyse the effectiveness of the use of medicinal plants as an alternative treatment for urinary tract infections through a comprehensive review of the bibliography. Methodology: The approach adopted was qualitative, allowing the analysis of ideas related to plants used in treating urinary tract infections. The study population consisted of published scientific papers and articles. A comprehensive search was carried out in scientific databases such as Google Académico, Elsevier, Dialnet and Scielo, covering publications between 2018 and 2023, selecting relevant literature based on the year of publication, keywords, results obtained and the language of the text. Results: Research reveals that the most commonly used plants for treating urinary tract infections are matte, eucalyptus, white flower, horse tail, and apple. In San José Iturbide, Mexico, a similar pattern was observed, with leaves prepared in infusion being the most used part. Colombian studies show that species such as Uncaria tomentosa and Sedum praealtum are rich in phenolic compounds and flavonoids, standing out for their antioxidant properties. American red myrtle has also been shown to be effective in reducing recurrent urinary tract infections. However, approximately 74% of users are unaware of the possible adverse effects of improper use of these plants, highlighting the need for education on their safe use.